2016
DOI: 10.1021/acs.joc.6b01722
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Controlled Stereodivergent, Enantioselective Conjugate Addition of 2-Oxazoline- and 2-Thiazoline-4-carboxylate to Nitroalkene Catalyzed by Chiral Copper Complexes

Abstract: The copper-catalyzed asymmetric conjugate addition of 2-oxazoline- and 2-thiazoline 4-carboxylate to a nitroalkene proceeded to give either the syn or anti adduct selectively in high enantiomeric excess when an appropriate chiral ligand was used. Subsequent reduction of the nitro group followed by hydrolysis of the oxazoline ring yielded an optically active gamma-lactam of protected alpha-quaternary serine derivative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The Fukuzawa's group further extended their diastereodivergent approach towards the Michael addition of 2‐oxazoline‐ and 2‐thiazoline‐4‐carboxylates 197 (analogues of 192 ) to nitroalkenes 24 (Scheme ) . The diastereodivergence was obtained by choosing appropriate chiral ligands with the copper(I) catalyst.…”
Section: Metal Complex‐catalyzed Diastereodivergent Reactionsmentioning
confidence: 99%
“…The Fukuzawa's group further extended their diastereodivergent approach towards the Michael addition of 2‐oxazoline‐ and 2‐thiazoline‐4‐carboxylates 197 (analogues of 192 ) to nitroalkenes 24 (Scheme ) . The diastereodivergence was obtained by choosing appropriate chiral ligands with the copper(I) catalyst.…”
Section: Metal Complex‐catalyzed Diastereodivergent Reactionsmentioning
confidence: 99%
“…Nitromethane conjugate addition products are commonly used to prepare biologically relevant heterocycles such as spiro‐γ‐lactams, pyrrolidines, and diarylpyrrolines and their isostere N ‐oxides . Thus, the reduction of the nitro groups of β‐(nitromethyl)chromones 2a – 2d was considered for the preparation of primary amine derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…Hou reported that tuning the electric properties of the phosphorus atoms on FOXAP ligands leads to chiral pyrrolidines via 1,3‐dipolar cycloaddition in exo and endo conformations, and each diastereomer was obtained with high selectivity . Asymmetric stereodivergent synthesis promoted by ferrocene‐type ligands was also developed by Cossío, Wang, and Fukuzawa . Because of these encouraging advances, the exploration of diastereomer‐specific ferrocenyl ligands is emerging.…”
Section: Discussionmentioning
confidence: 99%